2013
DOI: 10.2147/cia.s50238
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of vancomycin in elderly patients aged 75 years or older with methicillin-resistant Staphylococcus aureus hospital-acquired pneumonia

Abstract: BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) infections are associated with significant mortality and health care costs. To improve treatment outcomes for MRSA, a better understanding of the pharmacokinetic/pharmacodynamic parameters of vancomycin is required to develop optimal dosing strategies, particularly in elderly patients (≥75 years of age) with limited renal function. The purpose of this study was to determine whether pharmacokinetic indices for vancomycin are associated with mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Furthermore, elderly patients with MRSA pneumonia also have the potential to have worse clinical outcomes despite adequate vancomycin therapy, in part due to low albumin [19]. Therefore, if practicing at an institution that utilizes loading doses, consider a lower empiric maintenance dose to account for the serum accumulation over time, while still adjusting further maintenance dosing by utilizing serum concentrations or calculated AUC/MIC ratio of vancomycin [29, 68, 73]. …”
Section: Practical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, elderly patients with MRSA pneumonia also have the potential to have worse clinical outcomes despite adequate vancomycin therapy, in part due to low albumin [19]. Therefore, if practicing at an institution that utilizes loading doses, consider a lower empiric maintenance dose to account for the serum accumulation over time, while still adjusting further maintenance dosing by utilizing serum concentrations or calculated AUC/MIC ratio of vancomycin [29, 68, 73]. …”
Section: Practical Applicationsmentioning
confidence: 99%
“…Alternatively, equation-based monitoring can be programmed into the electronic medical system to automatically calculate the patient’s daily vancomycin AUC. Additionally, new evidence suggests that specific AUC/MIC goals may be better clinical markers of therapeutic efficacy [73]. In the general adult population, AUC/MIC ratio of >400 μg h/mL is targeted to provide effective therapy should the MRSA isolate have a vancomycin MIC ≤1 [9]; alternatively, the new proposed AUC/MIC targets of ≥521 on day 1 and ≥650 on day 2 should be sufficient for a 80–85% clinical success rate [36].…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present meta-analysis, several studies focused on elderly patients with nosocomial pneumonia and reported linezolid was associated with better efficacy compared with teicoplanin in elderly patients [27,29,[32][33][34]. We believe that higher clinical cure rate may contribute to better outcomes in elderly patients with nosocomial pneumonia because the immune system and organ function are often affected by aging and underlying diseases [41]. In contrast, teicoplanin have significant drawbacks which compromise their clinical usefulness for the treatment of serious MRSA infections.…”
Section: Discussionmentioning
confidence: 95%
“…Several antimicrobials used for the treatment of bacterial infections are excreted by the kidney, and this means that appropriate dosage adjustments should be applied whenever using these antimicrobials in elderly patients with CKD [7,8]. Dosage adjustments is required when creatinine clearance is lower than 50-60 ml/min [7 ,8], especially for those antimicrobials which may cause severe toxicity due to overexposure, namely aminoglycosides [37], vancomycin [38], levofloxacin [39] and cefepime [40]. Although reduced glomerular filtration rate (GFR) is often due to the combination of aging and chronic nephropathy damage [36], however the clinician should be aware that the finding of serum creatinine levels in the upper part of the normal range (i.e., 1.2 mg/dL) in an elderly patient may conceal moderate renal impairment (i.e., CLCr < 60 ml/min) [41].…”
Section: Antimicrobial Treatment Of Bacterial Infections In Frail Eldmentioning
confidence: 99%